Disagreement, Skepticism, and Begging the Question - Matheson, Jonathan (International journal for the study of skepticism, 2024)
In this paper, I examine Thomas Kelly’s account of the epistemic significance of bias presented in Bias: A Philosophical Study. Kelly draws a parallel between the skeptical threat from bias and the skeptical threat from disagreement, and crafts a response to these skeptical threats. According to Kelly, someone who is not biased can rely on that fact to conclude that their disagreeing interlocutor is biased. Kelly motivates this response by drawing several parallels to recent lessons in epistemology: that some question-begging reasoning is permissible, and that there are important asymmetries between epistemological good cases and bad cases. I argue that there are several reasons to resist Kelly’s response. In brief, there are problems with each of the motivations Kelly gives for his picture. Each parallel faces significant obstacles. In addition, his response also fails to take the new evil demon intuition seriously.